Effect of diesel late-injection on combustion and emissions characteristics of diesel/methanol dual fuel engine. (1st December 2018) - Wu, Taoyang; Yao, Anren; Yao, Chunde; Pan, Wang; Wei, Hongyuan; Chen, Chao; Gao, Jian
Highlights: Combustion, equivalence ratio, NOx and PM emissions were analyzed with diesel late-injection strategy. Number of nucleation mode particles increases slightly with higher MSR. Enhanced or retarded diesel late-injection can decrease NO x and accumulation mode PN simultaneously. Excessive or too delayed diesel late-injection is negative for nucleation mode particles in DMDF mode. Abstract: The late-injection strategy (close after main-injection) of common-rail diesel engine is capable of enhancing combustion turbulence and reducing particulate matter (PM) emissions. In this work, experimental study was performed to investigate the effect of diesel late-injection on combustion and emissions characteristics of diesel/methanol dual fuel (DMDF) engine. The experiments were carried out at a constant engine speed of 1340 rpm and a medium load of 1.0 MPa brake mean effective pressure (BMEP) with various methanol substitution ratio (MSR) on a common rail DMDF engine. The results reveal that higher MSR caused simultaneous decrease of nitric oxides (NO x ) and accumulation mode PM emissions in spite of late-injection strategy. In particular, an augment of up to 12.8% in nucleation mode particle number (PN) was observed as MSR increased from 15% to 50%. A small late-injection of diesel (<7.5 mg/cycle) had little impact on in-cylinder pressure and heat release rate (HRR). However, enhanced or retarded late-injection led to a decline in peak gas mean temperature (GMT) but an increase in later combustion temperature. With late-injection quantity (LIQ) increased from 1.5 mg/cycle to 7.5 mg/cycle, both NO x and accumulation mode PM decreased. Meanwhile, nucleation mode PM was almost unchanged and even rebounded slightly with overmuch LIQ (7.5 mg/cycle) in DMDF mode. Retarded late-injection led to a continuous reduction of 12.9% at most in NO x emissions in DMDF operation. As the interval between main-late injections (MLII) increased from 800 μs to 1200 μs, a trade-off relation appeared between nucleation mode and accumulation mode particles due to the mutual transformation of them. Furthermore, too delayed late-injection (MLII > 1200 μs) induced a simultaneous increase of particles with different size.